Social Construction of Social Studies Teachers Strengthening "Pancasila Student Profile" in Junior High Schools, Cirebon - Isaf, Hubeb; Wasino; Hamdan Tri Atmaja (Journal of Educational Social Studies, 2025)
The Strengthening of the Pancasila Student Profile Project (P5) is a character-building program for students implemented through the "Merdeka" curriculum. The application of P5 in junior high schools in Cirebon Regency has encountered issues due to various levels of understanding throughout the stages of socialization, internalization, and implementation. These differences have led to varied perceptions among teachers in constructing P5 activities. This paper aimed to analyse the social construction of Social Studies (IPS) teachers regarding P5, the implementation of P5 activities, and the analysis of students' social behaviour in junior high schools in Cirebon Regency. The study employed a qualitative research method with a phenomenological approach, using in-depth interviews and observations of P5 activities. The results showed that the social construction of Social Studies teachers varied, interpreting P5 as: (1) character and skill-strengthening activities, (2) product-oriented activities, both material and immaterial, and (3) a government program implemented according to the school’s capacity. The study concluded that these varying teacher interpretations influenced students' behaviour. This research provides significant insights into how P5 activities can impact students' social behaviour.